Indigo$1 (Bs star s - McKay, Hilary (New York : Margaret K. McElderry Books, 2004)
Spurred on by his youngest sister, Rose, twelve-year-old Indigo sticks up for himself and an American boy who has replaced him as the primary target of the school bullies.
First published: Great Britain : Hodder Children$1 (Bs Books, 2003.s
Ages 8-12.
Keywords: Bullies -- Fiction; Brothers and sisters -- Fiction; Friendship -- Fiction; Family life -- England -- Fiction; England -- Fiction